A comparison of fish communities between coves of varying connection to Harlan County Reservoir, Nebraska. Issue 1 (6th October 2022) - Mason, Brian E.; Wuellner, Melissa R.; Koupal, Keith D.
Abstract: Sediment berms of various heights have developed in the mouths of several coves within Harlan County Reservoir due to a combination of sediment deposition and lateral drift of eroded sediments. These berms can isolate coves from the main reservoir if the berm height is greater than the water elevation of the reservoir. Previous research in other reservoirs has shown that fish communities may differ in coves based on their connection histories. This study examines similarities and differences in fish assemblages between several disconnected coves and connected coves in Harlan County Reservoir. Connected coves had greater species richness and diversity compared to disconnected coves. Fish communities between cove types were relatively similar based on presence-absence data but notably different based on species abundance. Nonmetric multidimensional scaling ordination showed that fish communities were distinct between cove types. Eleven fish species were indicators of connected coves, and two species were indicators of disconnected coves. Disconnected coves had higher abundances of understudied native species rarely found in the main reservoir, such as Orangespotted Sunfish, Green Sunfish and Black Bullhead. Further research evaluating the influence of water quality, food availability, and duration of isolation is needed to understand the effect of cove disconnection on fish communities. Managers can use this information when planning cove renovations by weighing the costs and benefits of either maintaining ecologically distinct coves versus connecting coves and improving habitat accessibility for reservoir fishes.